2004
DOI: 10.1002/anie.200352772
|View full text |Cite
|
Sign up to set email alerts
|

Selective CH Bond Activation by a Supramolecular Host–Guest Assembly

Abstract: Interior design: A chiral supramolecular tetrahedral [Ga4L6]12− host (L=bis(bidentate) ligand) is shown to encapsulate a half‐sandwich iridium complex. This host–guest assembly reacts with aldehydes through CH bond activation, which occurs within the host interior. This activation occurs with high size and shape specificity as well as modest diastereoselectivity (d.r. 55:45–70:30) owing to the well‐defined shape of the host cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(123 citation statements)
references
References 29 publications
1
122
0
Order By: Relevance
“…34 (12) was prepared by addition of ethylene to a solution of 10 in CH 2 Cl 2 and is stable in aqueous solution, since the ethylene ligand is more strongly coordinating than water to the iridium center. As a consequence of this stability, 12 has decreased reactivity compared to neutral triflate species.…”
Section: Encapsulated Transition Metal Reactivitymentioning
confidence: 99%
“…34 (12) was prepared by addition of ethylene to a solution of 10 in CH 2 Cl 2 and is stable in aqueous solution, since the ethylene ligand is more strongly coordinating than water to the iridium center. As a consequence of this stability, 12 has decreased reactivity compared to neutral triflate species.…”
Section: Encapsulated Transition Metal Reactivitymentioning
confidence: 99%
“…70 A possible geometry of such a ligand is the triangle (C 3 -symmetry), which in combination with appropriate metal ions can form a tetrahedron. 71,72 Our approach was to use triangular ligands with catechol corners and octahedrally coordinating metal ions to obtain tetrahedra. [73][74][75][76][77] In the investigations the problem was addressed, if the ligands have to be rigid and highly preorganized, or if flexible ligands also can be manipulated in such a way that they lead to the desired oligonuclear structure and not only to mononuclear complexes (Fig.…”
Section: Tripodal Triscatechol Ligands For the Formation Of Mononuclementioning
confidence: 99%
“…41,42 While the 12-overall charge of 1 imparts water solubility, the naphthalene walls of the assembly provide a hydrophobic interior cavity, able to encapsulate guests, which is isolated from the bulk aqueous solution. A wide variety of small neutral and monocationic guests including aliphatic hydrocarbons, 43 protonated guests, 44 simple organic cations, 45 and reactive organometallic complexes [46][47][48] have been encapsulated in 1. Analysis of the mechanism for guest exchange revealed that 1 stays intact during the guest exchange process and that the apertures along the 3-fold axis of 1 dilate to allow for guest ingress and egress.…”
Section: Introductionmentioning
confidence: 99%
“…45 Using 1 to mediate the reactivity of organometallic guests, both stoichiometric and catalytic reactions have been carried out inside of 1 with both size-and stereo-selectivity. [46][47][48] Furthermore, 1 has been used as a catalyst for the sigmatropic rearrangement of enammonium cations. 49 We have recently reported the ability of 1 to greatly favor the protonated form of encapsulated substrates such as amines, with pK a shifts of up to 4.5 pK a units, and have exploited this stabilization for the catalysis of orthoformates and acetals in basic solution.…”
Section: Introductionmentioning
confidence: 99%